Structure of Mangrove Community and It΄s Relation to Macroepifauna Abudance in Intertidal Area of Rupat Straits Riau Province - Yudi Sastriawan; Thamrin '; Yusni Ikhwan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
AbstractObservation on mangrove vegetation density and abundance of macroepifauna was carried out in intertidal area Rupat straits Riau Province in October 2014. The purpose of this study was to determine the structure and mangrove density and it΄s relation to abudance of macroepifauna, it showed that the mangrove vegetation density ranged (2011,11-3044,44 trees/ha) with the highest density was found at station 2 (3044,44 trees/ha) followed by station 1 (2011,11 trees/ha). The abudance of macroepifauna was highest at station 2 (11244,44 ind/ha) followed by station 1 (1088,88 ind/ha). Correlation coeficient of mangrove density and abudance of macroepifauna appeared to be 0,695 and determination coeficient of 0,484, it was calculated that regression equation was y = - 5071 + 4,445x.Keyword : Mangrove, Macroepifauna, Rupat Channel, Density